Pengaruh Model Pembelajaran Three Level of Inquiry Untuk Meningkatkan Kemampuan Literasi Sains Siswa SMA - Dewi, Fadila Alma; Sa’adah, Sumiyati; Yusup, Iwan Ridwan (Edukhasi: Jurnal Inovasi Pendidikan, 2024)
Scientific literacy is the ability to understand scientific concepts and processes and use science to solve everyday problems which can be developed using the three level of inquiry learning model. This research aims to analyze the effect of the three level of inquiry learning model to improve students' scientific literacy skills in biodiversity material. This type of research is a quasi experiment with samples taken using a purposive sampling technique. The research results showed that the implementation of learning using the three level of inquiry model obtained a percentage score of 100% for teacher teaching activities and 97.7% for student learning activities. The increase in students' scientific literacy abilities in the experimental class and control class obtained an N-Gain value of 0.66 (medium) and 0.4 (medium), and a significance level of 0.003 <0.05 was obtained, which means there is a difference in the increase in students' scientific literacy abilities in classes with and without the three level of inquiry model. The results of student responses to learning obtained very good criteria with a percentage of 90%. Based on the research that has been conducted, it is concluded that the use of the three levels of inquiry learning model has a positive influence on increasing students' scientific literacy skills.